BEETHOVEN AT THE AGE OF 250 YEARS OLD- CENTRAL PILLAR OF CLASSICAL MUSIC CULTURE: CULT OF BEETHOVEN - GÜDEK, Bahar (Atlas Journal, 2020)
The year of 2020 is being celebrated as the year of Beethoven due to this year is the 250th birth day of this distinguished personality, mentioned as one of the most important names of the world music history and also described as one of the most influential music geniuses in all times. Beethoven as influencing not only the years he lived but also whole music history, guiding the music phases with the connection between classical music and romantic period and the most vocalized composer in the world continues to inspire musicians with his works. The privilege of Beethoven during music history is indicating the changes between the two periods and being a bridge for the following performers. He has succeeded in music to exemplify for the following glorious composers preparing the romance. So, it can be said that music has entered a new era with Beethoven. An artist who is no longer a craftsman suffers and peoduces; awarded not only with a superior ability but also with a higher soul than ordinary mortals, the artist suffers and produces for all humanity. Beethoven cult, whose origin dates back to the beginning of the nineteenth century and continues even in the 2020s. is perhaps the most central pillar of classical music culture. The ideas, even affected our view of music today may extend up to the yeast of the ideas surrounding the acceptance of Beethoven music. In this study, influencing the historical journey of classical music, became one of the central pillars of this music and the reasons why Beethoven and his music impress our point of view towards today’s music are discussed.